Circulating Cell Free DNA Testing. Issue 8 (August 2015) - Palomaki, Glenn E.; Kloza, E. M.; Lambert-Messerlian, G. M.; van den Boom, D.; Ehric, M.; Deciu, C.; Bombard, A. T.; Haddow, J. E.
<x xml:space="preserve">Abstract</x> ABSTRACT In terms of reliability of interpretation of cell-free DNA (cf DNA) screening for aneuploidy, "fetal fraction" (FF), or the proportion of cfDNA derived from the fetoplacental unit, is an important factor and is also the most common cause of failed or noninformative testing when samples have adequate plasma volume. Recent studies have indicated that a low FF is associated with specific abnormalities, and therefore these authors reexamined data from their previous study to investigate this outcome. The original study included 4664 women at 27 prenatal diagnostic centers, who, prior to invasive testing, provided plasma samples that were sent blindly to the Sequenom Center for Molecular Medicine. Test results were matched with outcomes tested at an independent laboratory. An expected FF was computed, and an FF multiple of the median was generated for the samples. The data were compared with a Gaussian distribution. A total of 2157 pregnancies were tested, and of those, 13 had an FF of less than 3.0%, including 3 trisomy 18 and 3 triploidy fetuses. In Down syndrome pregnancies, median FF was 17% higher (P < 0.001) when compared with euploid pregnancies. Because of a systemic upward shift, median FF in trisomy 18 pregnancies was 29% lower (P < 0.001). Median FF was comparable to those in euploid pregnancies for trisomy 13, monosomy X, sex trisomies, and mosaic fetuses. In triploid pregnancies, median FF was significantly lower (ratio, 0.19). Fetal fraction was less than 0.3 multiples of the median for 16 pregnancies (0.7%). The study confirmed previous findings that median FF in Down syndrome pregnancies is higher, and in pregnancies with trisomy 18, it is lower. Because laboratories vary in their methods of determining FF, some may be less suitable for this use. To confirm and refine these findings, other data should be further examined.